Contextualizing socio-legal problems of Sudanese youth in Malaysia: a case study - Kadouf, Hunud Abia (Sudan Knowledge, 2016)
Purpose Malaysia has become a major destination for Sudanese youth particularly for education purposes. There are however, some impending social problems that have erupted hence adversely affecting their existential relationship with the host society. The diversified nature of these problems has apparently transcended their entire expectations. This paper identifies the increasing challenges and prevalent social problems among Sudanese youth in Malaysia and gives suggestions for mutual acceptance and tolerance. Design/Methodology/Approach This study adopts mixed methodologies including qualitative, quantitative as well as comparative methods. The target groups are two categories of Sudanese Youth i.e., those who came at a mature age for study purposes (undergraduate, postgraduate and training) and those students -between the ages of 15 and 25years who were born in Malaysia. An attempt will also be made to engage in general discussions on the philosophy, concepts and theories of Diaspora in the light of the Sudanese youth’ precarious situation in Malaysia.